1989
DOI: 10.1136/pgmj.65.766.570
|View full text |Cite
|
Sign up to set email alerts
|

Meningeal infiltration by non-myelomatous IgD-secreting plasma cell dyscrasias

Abstract: Summary:Two cases of meningeal invasion by non-myelomatous plasma cel dyscrasias-a plasma cell leukaemia and an extramedullary plasmacytoma-are described. Both were secretors of IgD paraprotein and both were diagnosed in life, characteristics which we have not found in any other published case of plasma ceUl leptomeningitis. Analysis of our patients and of another 25 cases suggests as predisposing factors of meningeal invasion the male sex, presentation in the form of plasma cel leukaemia, presence of the IgD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…We found 37 case reports, describing isolated CNS MM cases, and two reports of series of 18 and 54 patients respectively (3, 4). The data of a total of 109 patients were reviewed (3–77).…”
Section: Resultsmentioning
confidence: 99%
“…We found 37 case reports, describing isolated CNS MM cases, and two reports of series of 18 and 54 patients respectively (3, 4). The data of a total of 109 patients were reviewed (3–77).…”
Section: Resultsmentioning
confidence: 99%
“…In 45 cases there were sufficient clinical data available to allow classification according to the staging system made by Durie and Salmon [49]; 5 cases (11%) had stage I disease, 11 (25%) stage II, and 29 (64%) stage III. MeM has earlier been correlated to high labeling index [50] and to PCL or circulating plasma cells [1,4,6,9,13,14,17,[25][26][27][28]. PCL have been reported to occur with a frequency of 1-5% of patients with MM, depending on the criteria used [17,51].…”
Section: Discussionmentioning
confidence: 99%
“…35,36 In our patient the CSF was shown by immunoelectrophoresis to contain the same type of paraprotein as in the serum. In the other cases in which CSF immunoelectrophoresis was performed, the same paraproteins were found in serum and CSF 3,9,12,13,21,31,36,39,40,45,46 except in one patient, whose serum and CSF had a kappa Bence-Jones protein but whose CSF alone had an IgA kappa paraprotein. 7 Accurate recognition of the plasma cells in CSF is very important for the diagnosis of meningeal involvement by MM.…”
Section: Volume 40 Number 3/may-june 1996mentioning
confidence: 82%
“…Although circulating plasma cells were never detected in our patient, they were detected in 14 cases 2,11,16,17,21,22,25,27,31,32,39,45,46 ; among these, 4 met the criteria for plasma cell leukemia. 2,27,31,45 Based on these data, Leifer et al 23 and Oda et al 32 suggested that myelomatous meningitis can originate in circulating plasma cells that spread to the meninges hematogenously.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation